Effect of SiO2 on rheology, morphology, thermal, and mechanical properties of high thermal stable epoxy foam. Issue 7 (31st October 2013) - Chen, Keping; Tian, Chunrong; Lu, Ai; Zhou, Qiuming; Jia, Xiaorong; Wang, Jianhua
ABSTRACT A series of highly thermostable epoxy foams with diglycidyl ether of bisphenol‐A and bisphenol‐S epoxy resin (DGEBA/DGEBS), 4, 4′‐diaminodiphenyl sulfone (DDS) as curing agent have been successfully prepared through a two‐step process. Dynamic and steady shear rheological measurements of the DGEBA/DGEBS/DDS reacting mixture are performed. The results indicate all samples present an extremely rapid increase in viscosities after a critical time. The gel time measured by the crossover of tan δ is independent of frequency. The influence of SiO2 content on morphology, thermal, and mechanical properties of epoxy foams has also been investigated. Due to the heterogeneous nucleation of SiO2, the pore morphology with a bimodal size distribution is observed when the content of SiO2 is above 5 wt %. Dynamic mechanical analysis (DMA) reveals that pure epoxy foam possesses a high glass transition temperature (206°C). The maximum of specific compressive strength can be up to 0.0253 MPa m3 kg−1 at around 1.0 wt % SiO2. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40068.